Komunikasi Jarak Jauh Antara Orang Tua Dan Anak: Studi Deskriptif Tentang Orang Tua Dengan Anak Yang Merantau Ke Kota Palembang - Ketrin Viola; Isna Wijayani (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
The purpose of this study was to determine how long distance communication between parents and children. This research method is qualitative with a descriptive approach to interview, observation, documentation, literature study. The theorynused inmthis researchnis the theorybof interpersonal communication andnthentheory of familynrelationshipnschemes. The subjects of this study consisted of informant 1 Vio Perori and her mother Mrs. Peronika from Air Putih Village, Informant 2 Andilau and her mother Ibu Suci from Kuala Sungai Pasir Village, and informant 3 Vivi Arinda and her mother Ibu Kartila from Sungai Pasir Village. Thenresearchnlocation was conducted in the respective informant's village. Thebresults of this studybshow that communicationnbetween parentsand children can be seen from the intensity of communication, students who have more communication intensity with their parents will be more familiar and vice versa. Supporting factors of the long-distance communication process between parents and children are the presence of means or means of communication such as telephones, pulses to communicate, free time, mutual understanding of limitations in communication, an open attitude about each other's circumstances and the environment that is not noisy. Meanwhile, inhibiting factors such as physical constraints, economic constraints and time constraints.